Disparities in psychosocial cancer care: a report from the international federation of psycho-oncology societies (2016)
Background The aim of the study was to understand the characteristics of the International Federation of Psycho‐oncology Societies (FPOS) and possible disparities in providing psychosocial care in countries where psycho‐oncology societies exist. Method A survey was conducted among 29 leaders of 28 countries represented within the FPOS by using a questionnaire covering (i) characteristics of the society; (ii) characteristics of the national health care system; (iii) level of implementation of psycho‐oncology; and (iv) main problems of psycho‐oncology in the country. Results Twenty‐six (90%) FPOS returned the questionnaires. One‐third reported to have links with and support from their government, while almost all had links with other scientific societies. The FPOS varied in their composition of members' professions. Psychosocial care provision was covered by state‐funded health services in a minority of countries. Disparities between countries arose from different causes and were problematic in some parts of the world (eg, Africa and SE Asia). Elsewhere (eg, Southern Europe and Eastern Europe), austerity policies were reportedly responsible for resource shortages with negative consequences on psychosocial cancer care. Half of FPOS rated themselves to be integrated into mainstream provision of care, although lack of funding was the most common complain. Conclusions The development and implementation of psycho‐oncology is fragmented and undeveloped, particularly in some parts of the world. More effort is needed at national level by strong coalitions with oncology societies, better national research initiatives, cancer plans, and patient advocacy, as well as by stronger partnership with international organizations (eg, World Health Organization and Union for International Cancer Control).